Monet - Bartolena, Simona (Masters of art (Prestel Verlag), 2011)
Monet's dazzling depictions of flowers, sunsets, fields, and oceans, in which line and shape are suggested through pure color, changed the way we perceive our natural surroundings. His numerous series, in which he depicts the same object at varying times of the day and in different seasons, pushed the limits of representational art. His final series of water lilies are considered to have ushered in the abstract movement of the twentieth century. Overflowing with images, this book offers full-page spreads of masterpieces as well as highlights of smaller details, allowing every aspect of the artist's technique and oeuvre to be appreciated. Chronologically arranged, the book covers important biographical and historic events that reflect the latest scholarship. Additional information includes a list of works, timeline, and suggestions for further reading. -- Book Description.